Utilization of Mount Osu Lombebua Stone in South Konawe Regency for Aus Layer Laston Mixture - Alfa Dionisius Patulak; Alpius; Monika Datu Mirring Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The utilization of Osu Lombebua mountain rock aggregate, South Konawe Regency has not been optimally utilized as a material in road pavement, especially in the Aus Layer Laston, starting from a problem, it is necessary to conduct research by conducting a series of characteristic tests with reference to the 2018 Highways Specification Standard. The characteristics of the Aus Layer Laston mixture by utilizing the rock aggregates of Mount Osu Lombebua, by knowing the characteristics of the aggregate, asphalt, and filler, then designing the composition of the mixture and making a test object in the form of Aus Layer Laston and the test Marshall Conventional for determining KAO after that making KAO test objects for Stability Marshall Time (SMS). The results of the study indicate that the characteristics of the pavement material in the form of rock aggregates of Mount Osu Lombebua, South Konawe Regency have met the General specifications of the Directorate General of Highways 2018. Based on the test of the characteristics of the mixture, Marshall Conventionalthe values ​​of Stability, flow, Void In Mix (VIM), Void In Mix Aggregate (VMA), and Foid Filled Bitumen (VFB) all meet the General Specifications of Highways 2018. Marshall Immersion test (Stability Marshall Remaining) on a mixture of meets the General Specifications of Highways 2018, where the value of Stability Marshall Remaining is 96,78 ≥ 90%.